Hubungan stres akademik dengan flow akademik pada mahasiswa - Annisa Gatari (Cognicia, 2020)
Students have various kinds of demands and obstacles on academic assignments that can make students experiencing academic stress. Academic stress make students feel uncomfortable, less focus, lack of concentration, and uncomfortable with academic activities which is called academic flow. The purpose of this was to determine the relationship between academic stress and academic flow in students. This research is a quantitative study with subjects being psychology students at the University of Muhammadiyah Malang 7st grade, and 174 subjects. The sampling technique used is nonprobability sampling, namely purposive sampling and analysis techniques using product moment correlation test with SPSS 24. The results of data analysis obtained the value of r = -,359, p = 0.000 (sig <0.01) meaning this study shows the relationship between the two variables and in accordance with the hypothesis that the higher the academic stress the lower the academic flow in students. Vice versa, the lower the academic stress, the higher the academic flow in students. The effective contribution of academic stress to academic flow is 12.9% and the remainder is 87.1%, influenced by other factors.